MicroRNAs involved in the HMGA2 deregulation and its co-occurrence with MED12 mutation in uterine leiomyoma - Mello, J. B.H. (2018)
STUDY QUESTION Can the mediator complex subunit 12 (MED12) mutation and high mobility group AT-hook 2 (HMGA2) overexpression co-occurrence be explained by the alternative mechanism of HMGA2 dysregulation in uterine leiomyomas (UL)? SUMMARY ANSWER The co-occurrence of MED12 mutation and HMGA2 overexpression, and a negative correlation of five validated or predicted microRNAs that target HMGA2 were reported. WHAT IS KNOWN ALREADY The recent stratification of UL, according to recurrent and mutually exclusive genomic alterations affecting HMGA2, MED12, fumarate hydratase (FH) and collagen type IV alpha 5-alpha 6 (COL4A5-COL4A6) pointed out the involvement of distinct molecular pathways. However, the mechanisms of regulation involving these drivers are poorly explored. STUDY DESIGN, SIZE, DURATION A total of 78 UL and 34 adjacent normal myometrium (NM) tissues was collected from 56 patients who underwent hysterectomies at a single institution. The patients were treated at the Department of Gynecology and Obstetrics, School of Medicine, Sao Paulo State University, Botucatu, SP, Brazil, from October 1995 to February 2004. PARTICIPANTS/MATERIALS, SETTING, METHODS Gene expression profiling was evaluated from fresh frozen tissues and compared with MED12 mutations at exon 2. In addition, RT-qPCR was applied to evaluate the expression levels of HMGA2 and their predictive miRNA regulators: hsa-let-7a, miR-26a, miR-26b, mir-93 and mir-106b. MAIN RESULTS AND THE ROLE OF CHANCE An unsupervised hierarchical clustering analysis revealed two main clusters with one of them (26 of 42 UL) showing an enrichment of MED12 mutated cases (18 of 26 UL). Increased expression levels of HMGA2 were observed in both clusters, including cases with MED12 mutation (cluster 1:18 UL). A significant HMGA2 overexpression (P < 0.001) in UL in comparison with NM was found. Five miRNAs predicted to regulate HMGA2 were significantly downregulated (P < 0.001) and negatively correlated to HMGA2 expression levels (P < 0.05) in UL. LIMITATIONS REASONS FOR CAUTION An in vivo functional study was not performed to validate the microRNAs and HMGA2 interaction due to technical limitations. WIDER IMPLICATIONS OF THE FINDINGS HMGA2 overexpression was detected in a significant number of MED12 mutated ULs, suggesting that these alterations coexist. Furthermore, five miRNAs were described as potential regulators of HMGA2 expression in UL. LARGE-SCALE DATA Data available in the Gene Expression Omnibus GSE42939. STUDY FUNDING AND COMPETING INTEREST(S) This study was supported by grants from Fundação de Amparo a Pesquisa do Estado de São Paulo (# 2008/58835-2) and Conselho Nacional de Pesquisa (# 485032/2007-4), Brazil. The authors declared having no conflicts of interest.